Functions of the Diary in Bram Stoker’s "Dracula" - Hlavacska, András; Krizsai, Fruzsina (Język. Komunikacja. Informacja, 2019)
Most papers analysing Bram Stoker’s Dracula concentrate on the Gothic tradition in which it is embedded, although another interesting feature of the novel is that it includes diary entries, logs, letters and other types of texts. Focusing on the complex issue of the novel’s genre, we use an interdisciplinary methodology based on Bakhtin’s theoretical work and the principles of functional pragmatics to highlight the importance of these text types, especially that of the diary, and to detect some of the special features of the genre. Diaries are not only texts produced in the scope of the narrative but they also function as a mental shelter, a moral obligation, and a weapon. We analyse metapragmatic reflections as signs of metapragmatic awareness belonging to the language act of writing or reading a diary. Finally, we underline the dynamic relation of the genre as an abstract category and as a concrete instance of that category in a text.